A Physiological Controller for Turbodynamic Ventricular Assist Devices Based on Left Ventricular Systolic Pressure. Issue 9 (19th September 2016) - Petrou, Anastasios; Ochsner, Gregor; Amacher, Raffael; Pergantis, Panagiotis; Rebholz, Mathias; Meboldt, Mirko; Schmid Daners, Marianne
Abstract: The current article presents a novel physiological feedback controller for turbodynamic ventricular assist devices (tVADs). This controller is based on the recording of the left ventricular (LV) pressure measured at the inlet cannula of a tVAD thus requiring only one pressure sensor. The LV systolic pressure (SP) is proposed as an indicator to determine the varying perfusion requirements. The algorithm to extract the SP from the pump inlet pressure signal used for the controller to adjust the speed of the tVAD shows robust behavior. Its performance was evaluated on a hybrid mock circulation. The experiments with changing perfusion requirements were compared with a physiological circulation and a pathological one assisted with a tVAD operated at constant speed. A sensitivity analysis of the controller parameters was conducted to identify their limits and their influence on a circulation. The performance of the proposed SP controller was evaluated for various values of LV contractility, as well as for a simulated pressure sensor drift. The response of a pathological circulation assisted by a tVAD controlled by the introduced SP controller matched the physiological circulation well, while over‐ and underpumping events were eliminated. The controller presented a robust performance during experiments with simulated pressure sensor drift.